2016
DOI: 10.4172/2167-0269.1000213
|View full text |Cite
|
Sign up to set email alerts
|

Real (or) Staged? Authenticity and Cultural Portrayal in Indigenous Tourism

Abstract: This study examined the perceptions of authenticity in cultural portrayals by both visitors and indigenous tourism operators in Far North Queensland. Surveys were administered over a two week period to indigenous tour operators and visitors at six locations throughout the region. The results showed that tourists place a high value on authenticity and the majority of them who had participated in an indigenous experience were satisfied with its level of authenticity. The study further found that the use of theat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The concept of "authenticity", and the impacts of the commodification of culture, have been discussed extensively in sustainable tourism and cultural tourism research (Engeset and Elvekrok 2015;Gnotha and Wang 2015;Kithiia and Reilly 2016;Taheri et al 2018;Park et al 2019;Shepherd 2002;Yeoman et al 2007). In the seminal work by Cohen (1988) on authenticity and commodification in tourism, it was suggested that the commoditization of culture incited by tourism can destroy the authenticity or meaning of cultural products for both locals and tourists alike.…”
Section: Covid-19 and Its Impact On Cultural And Sustainable Tourismmentioning
confidence: 99%
“…The concept of "authenticity", and the impacts of the commodification of culture, have been discussed extensively in sustainable tourism and cultural tourism research (Engeset and Elvekrok 2015;Gnotha and Wang 2015;Kithiia and Reilly 2016;Taheri et al 2018;Park et al 2019;Shepherd 2002;Yeoman et al 2007). In the seminal work by Cohen (1988) on authenticity and commodification in tourism, it was suggested that the commoditization of culture incited by tourism can destroy the authenticity or meaning of cultural products for both locals and tourists alike.…”
Section: Covid-19 and Its Impact On Cultural And Sustainable Tourismmentioning
confidence: 99%